HUBUNGAN MOTIVASI DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RSUD Dr.R.M. PRATOMO BAGANSIAPAPI TAHUN 2017 - Ria Irena (Universitas Pahlawan, 2017)
Motivation is an important factor for encouraging work, maintaining behavior, and channeling behavior in positive activities. A nurse must be motivated to have the quality of patient care, to develop nurse efficiency in carrying out nursing care. The purpose of this study was to determine the relationship between motivation and the performance of nurses in the Inpatient Room of RSUD Dr.R.M Pratomo in 2016. This study was a cross-sectional descriptive analytic design. The sample in this study were all nurses in the inpatient room of Dr.R.M Pratomo Hospital, amounting to 57 people. The sampling technique in this study was total sampling. The data collection tool used in this study is a questionnaire. The analysis used in this study is univariate and bivariate analysis with the chi square test. The results showed that the majority of respondents had low work motivation as many as 34 people (59.6%) and most respondents had low performance as many as 32 people (56.1%). Based on the chi square test, the results obtained there was a correlation between motivation and the performance of nurses in the Inpatient Room of RSUD Dr.R.M Pratomo in 2017 with p value 0.003 (<0.05). The results of the study are expected so that nurses always improve their performance so that they can improve the quality of hospital services